Mejoramiento de gestión universitaria basado en el Modelo de Sistema Viable. Caso de estudio: Universidad Libre - Ramirez Sanchez, Maria; Medina Garcia, Víctor Hugo; de la Fuente Garcia, David (Ingeniería, 2008)
This paper presents a methodology proposal based on the Viable System Model (MSV) which aims to study, design and offer specific mechanisms of viability, efficiency and improvement of university management. As an application of this model, a study case for the Libre University in Bogota is described. To develop this study a pilot plan has been developed for the improvement and organizational redesign, intended to focus on the administration of the university in order to make this institution an effective and viable organization. This Viable System Model is supported by a organization analysis theory known as "systematic approach".